2007
DOI: 10.1007/s00428-007-0480-x
|View full text |Cite
|
Sign up to set email alerts
|

Myxoinflammatory fibroblastic sarcoma: investigations by comparative genomic hybridization of two cases and review of the literature

Abstract: Myxoinflammatory fibroblastic sarcoma (MIFS) is a rare low-grade sarcoma of the distal extremities characterized by a myxohyaline stroma, a dense inflammatory infiltrate and virocyte- and lipoblast-like giant cells. Up to now, only two cases have been investigated cytogenetically, showing complex and heterogeneous karyotypes, in part with supernumerary ring chromosomes. We characterized two further cases of MIFS immunohistochemically and performed comparative genomic hybridization as well as DNA image cytometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…In an early report of MIFS, 2 cases were found to have chromosome 7 gains by comparative genomic hybridization, but the involved different regions (7q31q32 in one case; 7p15p21 in the other) did not encompass the BRAF locus (7q34). 34 Further investigations are needed to elucidate if BRAF amplification is a recurrent event in MIFS and is associated with any clinicopathologic features.…”
Section: Discussionmentioning
confidence: 99%
“…In an early report of MIFS, 2 cases were found to have chromosome 7 gains by comparative genomic hybridization, but the involved different regions (7q31q32 in one case; 7p15p21 in the other) did not encompass the BRAF locus (7q34). 34 Further investigations are needed to elucidate if BRAF amplification is a recurrent event in MIFS and is associated with any clinicopathologic features.…”
Section: Discussionmentioning
confidence: 99%
“…Most myxoinflammatory fibroblastic sarcomas show complex, near-diploid, or hypotriploid karyotypes [100][101][102][103]. CGH analyses showed gains of chromosome 7 in two cases [101].…”
Section: Myxoinflammatory Fibroblastic Sarcoma (Inflammatory Myxohyalmentioning
confidence: 97%
“…CGH analyses showed gains of chromosome 7 in two cases [101]. Distinctive abnormalities in myxoinflammatory fibroblastic sarcoma are the frequent presence of a balanced or unbalanced t(1;10) (p22;q24) translocation [100][101][102], ring chromosomes [102,103], and amplification of the chromosomal region 3p11-12 [103].…”
Section: Myxoinflammatory Fibroblastic Sarcoma (Inflammatory Myxohyalmentioning
confidence: 97%
“…Conventional and array CGH studies have shown the amplification of 3p11-12 (61,65). Notably, Hallor et al (61) demonstrated that 3p11-12 amplification is associated with an increased expression of VGLL3 and CHMP2B.…”
Section: Intermediate Soft Tissue Tumorsmentioning
confidence: 99%